2016
DOI: 10.7554/elife.17180
|View full text |Cite
|
Sign up to set email alerts
|

Tetherin is an exosomal tether

Abstract: Exosomes are extracellular vesicles that are released when endosomes fuse with the plasma membrane. They have been implicated in various functions in both health and disease, including intercellular communication, antigen presentation, prion transmission, and tumour cell metastasis. Here we show that inactivating the vacuolar ATPase in HeLa cells causes a dramatic increase in the production of exosomes, which display endocytosed tracers, cholesterol, and CD63. The exosomes remain clustered on the cell surface,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
135
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(147 citation statements)
references
References 39 publications
11
135
1
Order By: Relevance
“…Our findings of bafilomycin-stimulated EV release are in agreement with earlier observations showing increased secretion of lysosomal enzymes upon treatment with bafilomycin [53]. Bafilomycin-mediated stimulation of EV release was also observed in a recent paper [54], wherein it was also shown that in HeLa cells, exosomes are retained on the plasma membrane by the action of tetherin. These authors also demonstrated that treatment of cells with bafilomycin interrupts cholesterol trafficking leading to cholesterol accumulation in endosomes and exosomes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings of bafilomycin-stimulated EV release are in agreement with earlier observations showing increased secretion of lysosomal enzymes upon treatment with bafilomycin [53]. Bafilomycin-mediated stimulation of EV release was also observed in a recent paper [54], wherein it was also shown that in HeLa cells, exosomes are retained on the plasma membrane by the action of tetherin. These authors also demonstrated that treatment of cells with bafilomycin interrupts cholesterol trafficking leading to cholesterol accumulation in endosomes and exosomes.…”
Section: Discussionsupporting
confidence: 93%
“…As above, we saw the most striking increase in EV release following treatment with bafilomycin, which inhibits the V-ATPase proton pump and thereby allows the lumenal pH of lysosomes to rise over seconds to minutes [52]. The observed increase in CD63-EV release is consistent with previous reports of bafilomycin enhancing various types of EV release [47,53,54], effects that have been attributed to the pH neutralizing effects of inhibiting the V-ATPase. Curiously, however, we found that treating cells with chloroquine, which rapidly neutralizes lumenal pH as a weak base, did not have any effect on HANLCD63 release.…”
supporting
confidence: 90%
“…In this study, we demonstrate that HSC‐derived EVs transport PDGFRα, which is enriched in the EVs upon PDGF‐BB stimulation, suggesting a regulation mechanism for its trafficking, in addition to its degradation. Some prior studies show that degradation inhibition by bafilomycin A1 enhances EV release . In addition to this, here we demonstrate that degradation inhibition leads to further enrichment of EVs for PDGFRα and, in turn, blockage of PDGFRα enrichment in EVs enhances its degradation.…”
Section: Discussionsupporting
confidence: 84%
“…This is in agreement with the analysis of the cholesterol distribution in the endocytic pathway of B cells achieved by detection of cholesterol using immunoelectron microscopy, showing that cholesterol is mostly found in MVE ILVs and is released with exosomes . More recently, V‐ATPase inhibition by bafilomycin A1 was shown to induce a dramatic redistribution of cholesterol through exosome secretion in HeLa cells . Exosomes could thus be viewed as a way to regulate cellular cholesterol homeostasis, together with other cholesterol efflux mechanisms .…”
Section: Exosomes and Homeostasissupporting
confidence: 87%
“…Various studies have recently suggested that there is cross‐regulation between the exosomal pathway and lysosomal degradation. Lysosome inhibitors such as chloroquine or bafilomycin A1 have been shown to increase exosome release. Moreover, it was demonstrated that Atg5 dissociates V 1 V 0 ‐ATPase in endosomes, in turn decreasing endosomal acidification and promoting exosome secretion .…”
Section: Similarities Between Degradative and Secretory Mvesmentioning
confidence: 99%